Penyelesaian Konflik Internal antara Pemerintah Indonesia dengan Gerakan Separatisme di Papua melalui Mekanisme Horse-Trading: Internal Conflict Resolution between Government of Indonesia and Separatist Movement in Papua using Horse-Trading Mechanism - Sekar Wulan Febrianti; Ajeng Sekar Arum; Windy Dermawan; Akim Akim (Laboratorium Rekayasa Sosial, Jurusan Sosiologi, FISIP Universitas Bangka Belitung, 2019)
The study aims to analyze the process of internal conflict resolution between the Government of Indonesia and the separatist movement in Papua (Free Papua Movement (Indonesian: Organisasi Papua Merdeka or OPM)) using a horse-trading mechanism. This study was qualitative method by discussing the Free Papua Movement background and the conflict, then discussing the conflict process of timeline analysis tool to understand the development of its movement based on chronological order, and discussing the conflict resolutions that have been carried out with conflict mapping analysis tool to understand the actors that involved and their objectives. The conflict is the result of complexity among historical backgrounds, ideology, and a sense of injustice in Papua, on the other hand, the international community has increasingly supported Papua. Horse-trading has been used to resolve the conflict of Free Papua Movement and the Government of Indonesia, yet it has not yet reached a new resolution. The horse-trading mechanism effectively resolves the conflict when trust has been achieved between them to communicate both of them where they can deliver their objectives openly.